Protective Effect of Black Bean-Whey Double Protein Diet on Intestinal Barrier Injury Induced by Lipopolysaccharide in Rats - Weihong MENG; Zhiming LI; Jiayu ZHANG; Xin SHU; Defu LIANG; Kejin ZHUANG; Dongjie ZHANG (Shipin gongye ke-ji)
To explore the protective effects of a black bean-whey double protein (B-W double protein, B-W DP) diet on intestinal barrier injury induced by lipopolysaccharides (LPS) in rats. Sprague-Dawley rats were fed low, medium, and high doses of B-W DP for 28 d, and then, LPS was used to induce intestinal barrier injury. The intestinal morphology of the rats was observed using hematoxylin and eosin staining. The expression of tight junction proteins was quantified using immunohistochemistry, and the TLR4 and MyD88 expression levels were determined using real-time fluorescence quantitative polymerase chain reaction. Results showed that compared with low- and high-dose B-W DP, intermediate-dose B-W DP significantly (P<0.01) protected against intestinal barrier injury caused by LPS, increased villus length by 26.69%, reduced crypt depth by 22.61%, and increased their ratio by 46.78%. Three doses of B-W DP regulated tight junction proteins in different manners, and the intermediate dose exhibited the most significant effect (P<0.01), increasing ZO-1, Claudin-1, and Occludin expression levels by 14.32%, 31.80%, and 16.67%, respectively. Three doses of B-W DP significantly inhibited the inflammatory pathway (P<0.01), and the intermediate dose exhibited the most significant effect, reducing TLR4 and MyD88 protein levels by 37.25% and 33.04%, respectively. In summary, a moderate dose of B-W DP can improve intestinal morphology, intestinal digestion, and absorption capacity, increase the expression of tight junction proteins, maintain the integrity of epithelial cells, reduce intestinal permeability, downregulate TLR4 and MyD88 protein expression, and alleviate inflammatory reactions. All of which exhibit effective protective effects on LPS-induced intestinal barrier injury.